Mingling with the enemy : a social survival guide for our politically divided era - Martinet, Jeanne, 1958- (New Harbinger Publications, Inc., 2020)
"Many people need help navigating conversational minefields such as politics and religion--without getting blown up. Mingling with the Enemy is a vital guide for "surviving" contentious arguments, promoting civil discourse, and finding common ground in any social setting--from cocktail parties to PTA meetings. With this go-to guide, readers will learn how to successfully intermingle, listen, and diffuse heated arguments or disagreements while remaining respectful."--